The spectrum of BRCA1 and BRCA2 pathogenic sequence variants in Middle Eastern, North African, and South European countries. Issue 11 (26th July 2019) - Laitman, Yael; Friebel, Tara M.; Yannoukakos, Drakoulis; Fostira, Florentia; Konstantopoulou, Irene; Figlioli, Gisella; Bonanni, Bernardo; Manoukian, Siranoush; Zuradelli, Monica; Tondini, Carlo; Pasini, Barbara; Peterlongo, Paolo; et al.
Abstract: BRCA1 BRCA2 mutational spectrum in the Middle East, North Africa, and Southern Europe is not well characterized. The unique history and cultural practices characterizing these regions, often involving consanguinity and inbreeding, plausibly led to the accumulation of population‐specific founder pathogenic sequence variants (PSVs). To determine recurring BRCA PSVs in these locales, a search in PUBMED, EMBASE, BIC, and CIMBA was carried out combined with outreach to researchers from the relevant countries for unpublished data. We identified 232 PSVs in BRCA1 and 239 in BRCA2 in 25 of 33 countries surveyed. Common PSVs that were detected in four or more countries were c.5266dup (p.Gln1756Profs), c.181T>G (p.Cys61Gly), c.68_69del (p.Glu23Valfs), c.5030_5033del (p.Thr1677Ilefs), c.4327C>T (p.Arg1443Ter), c.5251C>T (p.Arg1751Ter), c.1016dup (p.Val340Glyfs), c.3700_3704del (p.Val1234Glnfs), c.4065_4068del (p.Asn1355Lysfs), c.1504_1508del (p.Leu502Alafs), c.843_846del (p.Ser282Tyrfs), c.798_799del (p.Ser267Lysfs), and c.3607C>T (p.Arg1203Ter) in BRCA1 and c.2808_2811del (p.Ala938Profs), c.5722_5723del (p.Leu1908Argfs), c.9097dup (p.Thr3033Asnfs), c.1310_1313del (p. p.Lys437Ilefs), and c.5946del (p.Ser1982Argfs) for BRCA2 . Notably, some mutations (e.g., p.Asn257Lysfs (c.771_775del)) were observed in unrelated populations. Thus, seemingly genotyping recurring BRCA PSVs in specific populations may provide first pass BRCA genotyping platform. Data Repository Information: LOVD: https://databases.lovd.nl/shared/variants#order=VariantOnGenome&search_VariantOnGenome/Reference=Laitman